HAK ATAS BANTUAN HUKUM DALAM SISTEM PERADILAN PIDANA: KAJIAN NORMATIF TERHADAP AKSES KEADILAN - Azizah Ghafur Silalahi; Arini Syafitri; Yudi Krismen (STKIP Subang, 2026)
The right to legal aid is an important part of human rights protection and the rule of law principle in the criminal justice system. This research aims to analyze the normative arrangement of the right to legal aid, its implementation in the practice of criminal justice, normative and structural obstacles in access to legal aid, as well as the reconstruction of the strengthening of legal aid to realize access to justice in Indonesia. This research uses a normative legal research method with a legislative, conceptual, and analytical approach. Legal materials are obtained through the study of literature on laws and regulations, international legal instruments, books, scientific journals, and relevant research results. The research results show that the right to legal assistance has gained constitutional legitimacy through the 1945 Constitution and is further regulated in the Criminal Code and Law Number 16 of 2011 concerning Legal Assistance. However, the implementation is still facing various obstacles, such as regulatory disharmony, limited legal aid organizations, lack of quality and distribution of advocates, low public legal awareness, weak supervision of law enforcement officers, and limited state budget. In addition, formalistic administrative procedures and access inequality in remote areas cause legal assistance to not be fully accessible evenly. This research emphasizes the need to reform the legal aid system through the harmonization of regulations, institutional strengthening of legal aid organizations, improving the quality of human resources, optimizing digital technology, as well as strengthening the role of paralegals and public legal education so that access to justice can be realized substantively and inclusively.